Social and organizational developments through emerging e-government applications : new principles and concepts - Weerakkody, Vishanth (Hershey, PA : Information Science Reference, 2010)
'This book offers reflective accounts of the key research themes that have emerged in the last few years as electronic government services have become commonplace in the world'--Provided by publisher.
'Premier reference source'--Cover.
Includes bibliographical references and index.
Keywords: Internet in public administration